RUMUSAN STRATEGI PENGEMBANGAN PERUMDA AIR MINUM TIRTA SENENTANG BERDASARKAN HASIL EVALUASI KINERJA - Elsy Ivana Clara Ivana; Stefanus Barlian Soeryamassoeka; Herawati Henny (UKI Press, 2023)
Water is part of our daily life needs. To meet the need for clean water in Sintang Regency, PERUMDA Tirta Senentang Drinking Water uses 4 water sources, namely from the Kapuas River, Melawi River, Ketungau River, Kayan River with a total capacity of 295 lt/sec. This research aims to find and formulate strategies in efforts to develop the performance of PERUMDA Air Minum Tirta Senentang as a clean water supply agency based on the results of performance evaluations. The analytical method used in this research is performance evaluation analysis using the Balanced Scorecard method by paying attention to four aspects, namely financial aspects, service aspects, operational aspects and human resource aspects. And for analysis of the formulation of strategies in efforts to develop performance using SWOT analysis. Based on the performance evaluation, the results obtained from a series of SWOT analyzes are the strategy formulation that best suits the performance development efforts of PERUMDA Air Minum Tirta Senentang, namely by optimizing Strengths so that existing opportunities can be maximized so that six strategy formulations are obtained for strengthening and implementing regulations in the development of PERUMDA Water Drink Tirta Senentang. From the results of the QSPM analysis, an alternative strategy with the best policy was obtained, accompanied by determining the time period, a short-term strategy was obtained, namely increasing service coverage, production capacity and service blocks. The medium term strategy is to optimize the home connection network and idle capacity. And the long-term strategy is to collaborate with competent parties.Keywords: SWOT analysis ; Performance evaluation ; Tirta Senentang Drinking Water Municipal Corporation.